‘A wound that aches yet isn’t felt ... a pain that rages without hurting’: Getting to know the identity of outsourced housekeepers through the bond of memory and social class - Viviani Teodoro dos Santos; Marivânia Conceição de Araújo; Marcio Pascoal Cassandre (Ciências Sociais Unisinos)
Dealing with identities means facing multiple ways of walking a pathway. Each collective, each paradigm, each historical period, carries its own capacity to bring up new perspectives to the theme of identities. Bearing such assumption as standpoint and keeping interest for a collective or occupational identity, we aimed to know identity elements of an outsourced housekeeper group in a Brazilian federal public institution. In order to do so, we used the perspective of memory as an aid in the process of revelation and constituent element of identities, as well as the context of social class to seek the understanding of the reality learned in the field. As methodological procedures, we used a semi-structured interview with the cleaning team supervisor, two focus groups, individual narrative interviews with the eight housekeepers and a brief period of participant observation. The confirmation was that past memories are an essential part of understanding this collective identity and that the group has in common a profession that does not come from a choice based on skills or vocation, but from conditions of social vulnerability. The identity of the group is marked by: dramatic events, however, surrounded by gestures of solidarity; an intense and heavy daily work, marked by the hierarchy of distinctions; and a trajectory that is based on elements such as faith and daily dedication, so that, when playing a role in the system, they need to use conformism as a survival strategy.